Normobaric hyperoxia training in elite female hockey players - Murray, K.; Sommerville, A.; McKenna, M.; Edgar, G.; Murray, A. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Supplemental oxygen use may offer recovery benefits to team sport athletes both in training and match play. A blinded independent measures study was used to investigate the effect of supplementary oxygen use during recovery from high-intensity exercise on performance.